Complexity Management with the K-Method Price Structures, IT and Controlling for Procurement of Packaging Materials - Kossmann, Daniel; Kossmann, Donald; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
The book describes the K-Method developed by the authors. The purpose of the K-Method is to negotiate and manage a complex portfolio of customised materials all belonging to the same purchasing group (e.g. labels). The underlying idea is to agree on prices for specification features, instead of giving each material an individual price based on its unique specifications. By doing so, a price formula is agreed to between the buyer and the supplier which can even define the prices of future materials with any kind of specification.
Preface -- Acknowledgements -- Introduction to the Book -- Definitions and typical issues -- The K-Method, example of a price formula -- Solutions for big issues using the K-Method -- Reasonig for the introduction of the K-Method -- The K-Method and other industries -- Outlook on advanced technologies -- Specific issues when designing a price formula -- Implementation in the ERP system -- Specification features of selected categories -- Value analysis -- Step prices -- Consistent prices -- Deduction of the price formula.
Keywords: Business; Industrial procurement; Computer simulation; Management information systems; Computer science; Business and Management; Procurement; Simulation and Modeling; Management of Computing and Information Systems; Electronic books